2018
DOI: 10.1371/journal.pone.0198221
|View full text |Cite
|
Sign up to set email alerts
|

AmpliSeq transcriptome analysis of human alveolar and monocyte-derived macrophages over time in response to Mycobacterium tuberculosis infection

Abstract: Human alveolar macrophages (HAM) are primary bacterial niche and immune response cells during Mycobacterium tuberculosis (M.tb) infection, and human blood monocyte-derived macrophages (MDM) are a model for investigating M.tb-macrophage interactions. Here, we use a targeted RNA-Seq method to measure transcriptome-wide changes in RNA expression patterns of freshly obtained HAM (used within 6 h) and 6 day cultured MDM upon M.tb infection over time (2, 24 and 72 h), in both uninfected and infected cells from three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(82 citation statements)
references
References 69 publications
(72 reference statements)
14
68
0
Order By: Relevance
“…Additionally, the transcriptional signature observed in AMTBs in response to Mtb infection was associated with myeloid cell inflammation and TREM1 signaling as a topscoring canonical pathway across all macrophage populations evaluated in this study (AMCTs, AMTBs, and SMs) ( Figure 6A). Our findings are in line with recently published reports (15), indicating TREM1 as a top inflammatory signaling pathway playing a critical role in controlling inflammatory processes.…”
Section: Ams Of Tb Patients Respond To Infection With Virulent Mtb CLsupporting
confidence: 94%
See 1 more Smart Citation
“…Additionally, the transcriptional signature observed in AMTBs in response to Mtb infection was associated with myeloid cell inflammation and TREM1 signaling as a topscoring canonical pathway across all macrophage populations evaluated in this study (AMCTs, AMTBs, and SMs) ( Figure 6A). Our findings are in line with recently published reports (15), indicating TREM1 as a top inflammatory signaling pathway playing a critical role in controlling inflammatory processes.…”
Section: Ams Of Tb Patients Respond To Infection With Virulent Mtb CLsupporting
confidence: 94%
“…Although the results of previous studies have provided a framework for understanding the consequences of macrophage-Mtb interaction, relatively little data are available regarding human AMs collected from healthy individuals (14,15), while no data have been obtained from AMs from TB patients. So far, most of our knowledge from the interaction of Mtb with MPS cells has been garnered by the use of monocyte-derived macrophages (MDMs) from healthy individuals (14,(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that established in vitro models do not adequately replicate the initial host response to Mtb. In addition, it is worth noting that our observations that murine AMs become more pro-inflammatory over time in culture (data not shown) are in concordance with reports that the response of human AMs to Mtb infection evolves from a profile unique to AMs towards one that is more similar to that of monocytes the longer they are cultured in vitro ( 44 ).…”
Section: Discussionsupporting
confidence: 92%
“…Considering the dramatic perturbation of the macrophage by intracellular mycobacteria, we and others have demonstrated that bovine and human alveolar macrophage transcriptomes are extensively reprogrammed in response to infection with M. bovis and M. tuberculosis Vegh et al, 2015;Lavalett et al, 2017;Jensen et al, 2018;Malone et al, 2018;Papp et al, 2018). These studies have also revealed that differentially expressed gene sets and dysregulated cellular networks and pathways are functionally associated with many of the macrophage processes described above that can control or eliminate intracellular microbes.…”
Section: Introductionmentioning
confidence: 81%